Des inégalités économiques à la justice sociale : l’influence de John Rawls sur Thomas Piketty - Benoît Walraevens (Œconomia, 2024)
This article studies Thomas Piketty’s relationship with the American philosopher John Rawls and his theory of justice as fairness, in order to gain a better understanding of the characteristics of the French economist’s conception of social justice and of his views on the role of the social scientist in the public arena. We begin by looking at the various references to Rawls in Piketty’s work, in an attempt to show how this allows us to better grasp the evolution of the French economist’s thinking. We then analyse their respective principles of justice and the socio-economic models likely to embody these principles, focusing on property-owning democracy. Finally, we examine their views on redistributive taxation. Through the work of Thomas Piketty, one of today’s most influential economists, we consider the legacy of Rawls and the Theory of Justice in economics, more than fifty years after its publication.